KAP Study Regarding Common Diseases Among Rural Women Inhabiting Some Semi Arid Areas of Rajasthan - Singh, madhu B; Lakshminarayanna, J; Haldiya, K R (Annals of Arid Zone, 2016)
In this study 391 elderly women inhabiting semi arid areas of Rajasthan were interviewed and the information is gathered on their knowledge. attitude and practices of common diseases. It is revealed from the study that none of the women observed in the category of "Knows all" about the causes. preventive and curative measures of different diseases. Overall knowledge and awareness of different diseases is very poor except for Fever. Diarrhoea and Malaria indicating a need of health education programmes to be organised at village level by health workers.